Reconstruction of the sternum. - Olazábal, Alberto; Juri, Héctor; Acosta, Fernando; Cassinasco, Angeles (Cirugía del Uruguay, 1987)
lnfection and dehiscence of median sternotomy, though rare, has a high morbimortality if ísn't adqua• tely treated. In those patients that don't improve wlth the closed irrigation technique and that before were opened and packed with gauze, wlth high risk and prolonged hospltalization. We have had excellent results with the use of muscle flaps. In our small serie of 8 patients, we have treated 2 cases of mediastinitis and dehiscense of sternotomy and 6 cases of chronic suppurative sternochondrltis without mortality. The shortage of hospitalization time is other of the benefits that derives from the use of these procedures.